BpNAC012 Positively Regulates Abiotic Stress Responses and Secondary Wall Biosynthesis. Issue 2 (10th December 2018) - Hu, Ping; Zhang, Kaimin; Yang, Chuanping
Abstract : BpNAC012 is a transcriptional regulator of both abiotic stress responses and secondary wall biosynthesis. Abstract: NAC (NAM, ATAF1/2, and CUC2) transcription factors play important roles in plant biological processes and stress responses. Here, we characterized the functional roles of BpNAC012 in white birch ( Betula platyphylla ). We found that BpNAC012 serves as a transcriptional activator. Gain- and loss-of-function analyses revealed that the transcript level of BpNAC012 was positively associated with salt and osmotic stress tolerance. BpNAC012 activated the core sequence CGT[G/A] to induce the expression of abiotic stress-responsive downstream genes, including Ɗ-1-pyrroline-5-carboxylate synthetase, superoxide dismutase, and peroxidase, resulting in enhanced salt and osmotic stress tolerance in BpNAC012 overexpression transgenic birch lines. We also showed that BpNAC012 is expressed predominantly in mature stems and that RNA interference-induced suppression of BpNAC012 caused a drastic reduction in the secondary wall thickening of stem fibers. Overexpression of BpNAC012 activated the expression of secondary wall-associated downstream genes by directly binding to the secondary wall NAC-binding element sites, resulting in ectopic secondary wall deposition in the stem epidermis. Moreover, salt and osmotic stresses elicited higher expression levels of lignin biosynthetic genes and elevated lignin accumulation in BpNAC012 overexpression lines. These findings provide insight into the functions of NAC transcription factors.